Effect of exercise training for five years on all cause mortality in older adults—the Generation 100 study: randomised controlled trial. (7th October 2020) - Stensvold, Dorthe; Viken, Hallgeir; Steinshamn, Sigurd L; Dalen, Håvard; Støylen, Asbjørn; Loennechen, Jan P; Reitlo, Line S; Zisko, Nina; Bækkerud, Fredrik H; Tari, Atefe R; Sandbakk, Silvana B; Carlsen, Trude; et al.
Abstract: Objective: To evaluate the effect of five years of supervised exercise training compared with recommendations for physical activity on mortality in older adults (70-77 years). Design: Randomised controlled trial. Setting: General population of older adults in Trondheim, Norway. Participants: 1567 of 6966 individuals born between 1936 and 1942. Intervention: Participants were randomised to two sessions weekly of high intensity interval training at about 90% of peak heart rate (HIIT, n=400), moderate intensity continuous training at about 70% of peak heart rate (MICT, n=387), or to follow the national guidelines for physical activity (n=780; control group); all for five years. Main outcome measure: All cause mortality. An exploratory hypothesis was that HIIT lowers mortality more than MICT. Results: Mean age of the 1567 participants (790 women) was 72.8 (SD 2.1) years. Overall, 87.5% of participants reported to have overall good health, with 80% reporting medium or high physical activity levels at baseline. All cause mortality did not differ between the control group and combined MICT and HIIT group. When MICT and HIIT were analysed separately, with the control group as reference (observed mortality of 4.7%), an absolute risk reduction of 1.7 percentage points was observed after HIIT (hazard ratio 0.63, 95% confidence interval 0.33 to 1.20) and an absolute increased risk of 1.2 percentage points after MICT (1.24, 0.73 to 2.10). When HIIT was compared with MICT as reference group an absolute risk reduction of 2.9 percentage points was observed (0.51, 0.25 to 1.02) for all cause mortality. Control participants chose to perform more of their physical activity as HIIT than the physical activity undertaken by participants in the MICT group. This meant that the controls achieved an exercise dose at an intensity between the MICT and HIIT groups. Conclusion: This study suggests that combined MICT and HIIT has no effect on all cause mortality compared with recommended physical activity levels. However, we observed a lower all cause mortality trend after HIIT compared with controls and MICT. Trial registration: ClinicalTrials.gov NCT01666340 .